Bird-related fault analysis and prevention measures of ±400 kV Qinghai-Tibet DC transmission line - Yujian Ding (Elsevier, 2021)
Birds’ activities may cause short-circuit damages of transmission line (TL), especially in the areas without tall trees and other vegetation. ±400 kV Qaidam-Lhasa DC TL with an average altitude of about 4650 m in China is the highest DC TL in the world. Since November 2011 to the end of January 2017, there have been a total of 102 short-circuit damages, including 95 damages caused by birds. The damages were mainly caused by the defecation of birds. This paper analyzes the characteristics and causes of flashover damages of the Project. Moreover, A survey of birds along the TL was carried out by using line transect method and point count method, and then the comprehensive improvement measures for such bird-related outages were put forward. The results show that a total of 26 species of birds are involved in the damages, mainly including large or clustered birds such as Gyps himalayensis, Aegypius monachus, Buteo hemilasius, Buteo buteo and Corvus corax. The damages often occur at night in winter and spring. The prevention measures shall be dominated by guiding type and supplemented by isolation type and expulsion type, and focus on the treatment of tension tower. Through improvement, the outages have been greatly reduced from 2018 to now.